Managerial responses to customer measurement - Shaw, Robert (Henry Stewart Talks, 2008)
Good practice customer management process, Measurement, who does it and how, Interpretation, who is the interpreter, Feedback: who, when, what and how, Response: when to ignore feedback and how to decide appropriate action